2020
DOI: 10.3389/fpsyg.2020.02036
|View full text |Cite
|
Sign up to set email alerts
|

When Emergency Patients Die by Suicide: The Experience of Prehospital Health Professionals

Abstract: The suicide of a patient can be a disturbing experience for health professionals. According to literature, a patient suicide is a professional hazard in the path of prehospital emergency professionals. In the emergency context, several factors pointed out in literature as predictors of increased emotional impact and more severe traumatic reactions are present. However, the impact of patient suicide on prehospital emergency professionals is still an understudied subject. The aim of this study was to better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“… 34 Indeed, Rothes et al (2020) reported such professional growth and increased awareness in paramedics following their experiences with patients who died by suicide, but this relied on supportive cultures, training and preparation to overcome the negative emotional impact. 35 Once again, tragic and costly choices may be required to invest resources and mental energies in these issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 Indeed, Rothes et al (2020) reported such professional growth and increased awareness in paramedics following their experiences with patients who died by suicide, but this relied on supportive cultures, training and preparation to overcome the negative emotional impact. 35 Once again, tragic and costly choices may be required to invest resources and mental energies in these issues.…”
Section: Resultsmentioning
confidence: 99%
“…It should however be recognised that such growth relies on supportive cultures, training and preparation to overcome the negative emotional impact. 35 Future preparation for pandemics should therefore consider the findings of this study and focus on such issues in planning.…”
Section: Discussionmentioning
confidence: 96%
“…Two recent articles have provided some early evidence relating to the impact that attending suicides, such as hangings, has on EMS clinicians, including the lasting emotional impact and the desire for better training, as well as a recognition of the impact on bystanders and family members ( Nelson et al, 2020 ; Rothes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not only social workers, relatives and teachers can be stunned, overwhelmed and helpless in these situations but also health care professionals are. Social workers and emergency service providers dealing with these highly stressful situations may themselves be traumatized by this confrontation and may suffer significant psychological damage ( 1 3 ). In adult as well as in child and adolescent mental health emergencies, self-mutilating and suicidal behavior are within the most frequent challenges as documented in the analyses of Franzen et al and Slankamenac et al within this issue.…”
mentioning
confidence: 99%